Linking Faith Based Culture and Managerial Skills to Fi-nancial Performance: Evidence from Islamic Banks - Hendrik Tri Oktaviansyah; Bayu Wijayantini; Alfi Arif; Robby Reza Zulfikri; Taufik Sobri; Husam A. Y Abusaada (Indonesian Journal Publisher, 2025)
The growth of Islamic banking in Indonesia reflects the increasing demand for financial systems that align with faith-based values and ethical management practices. Within this context, the success of Islamic banks depends not only on financial instruments but also on how Islamic culture and managerial capability shape employee motivation and performance. This study aims to examine the influence of Islamic organizational culture and managerial capability on financial performance, with work motivation as a mediating variable. A quantitative method was employed using primary data collected from 80 employees of Bank Syariah Indonesia (BSI). The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and indirect relationships among the variables.The results reveal that Islamic organizational culture and managerial capability significantly enhance employee motivation, improving performance and strengthening the bank’s financial outcomes. Work motivation partially mediates the relationships between Islamic values, managerial competence, and financial performance.This study emphasizes the need for Islamic banks to integrate faith-based culture with managerial excellence to build motivated, ethical, and high-performing employees. The findings contribute to Islamic finance scholarship by demonstrating that spiritual and behavioral dimensions within organizations can yield.